Alternative energy sources, materials and technologies selected, peer reviewed papers from the International Conference on "Sustainable Energy Resources, Materials and Technologies" (ISERMAT 2015), January 8-9, 2015, Chennai, India - Nallusamy, N.; Suresh, M.; Rajkumar, S.; Lakshminarayanan, A.K (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the International Conference on "Sustainable Energy Resources, Materials and Technologies" (ISERMAT 2015), January 8-9, 2015, Chennai, India. The 181 papers are grouped as follows: Chapter 1: Renewable Energy, Environment and Heat Transfer; Chapter 2: Modeling and Simulation; Chapter 3: Materials Properties Research and Processing; Chapter 4: Composite Materials Characterization;Chapter 5: Engines and Alternative Fuels;Chapter 6: Electrical Energy Systems and Devices; Chapter 7: Measurements and Testing Keywords: Alternative Energy Sources, Energy Storage, Thermodynamic, Heat Transfer, Wind Turbine, Diesel and Biodiesel Fuels, Engines, Fuel Consumption Contributors from the wide range of disciplines and professions that touch upon alternative energy present about 175 papers on renewable energy, the environment, and heat transfer; modeling and simulation; materials properties, research, and processing; characterizing composite materials; engines and alternative fuels; electrical energy systems and devices; and measurement and testing. Among specific topics are evaluating the performance of a photovoltaic system in humid atmosphere, analyzing a wind turbine aerodynamic braking system using chord wise spacing, the effect of swirl on the performance of an annular diffuser, mitigating wear in cast magnesium alloy through friction-stir surface compositing reinforced with fly ash, and the influence of engine speed on mixing and emission characteristics of multiple-injection common rail direct injection diesel engine. -- Alternative engergy-- Energy engineering-- Materials science.